The Impact Of English-only And Code-switching Task-based Oral Activities On English Language Learners’ Willingness To Communicate - Irum, Fatima (2021)
Due to the exponential growth of English as a global language, students from different countries of the world including Pakistan are required to command over this language. In this regard, the potentially beneficial role of Willingness to Communicate (WTC) in learning the English language is gradually becoming acknowledged in the second language acquisition research (SLA) and communication. To this end, few interventional studies have attempted on how to help language learners enhance their WTC in the English language. Drawing on the principles of task-based language teaching, this mixed-method research primarily aimed at investigating the impact of task-based oral activities on Pakistani undergraduates’ WTC in the English language by randomly recruiting three intact classes and allocating them in three groups: task-based oral activities With English-only experimental group, task-based oral activities with code-switching experimental group, and the control group. By integrating English-only and code-switching practices in the intervention, this study sought to test the effectiveness of two distinct medium of communication within task-based learning settings for constructing a framework in relation to learners’ WTC. For collecting the data for the quantitative phase of this study, McCroskey’s (1992) WTC questionnaire served as pre- and post-test, whereas the qualitative phase of this study involved semi-structured interviews. To analyse the quantitative data, Independent Samples t-test, paired Samples t-test, One-way ANCOVA,